Bisphosphonate Use and Fractures in Adults with Hypophosphatasia. (26th August 2019) - Rassie, Kate; Dray, Michael; Michigami, Toshimi; Cundy, Tim
ABSTRACT: Adults with hypophosphatasia (HPP) may suffer femoral fractures resembling the atypical femoral fractures that can occur with long‐term bisphosphonate treatment, and there is an emerging consensus that bisphosphonates should not be used in adults with HPP and low bone mass. However, the spectrum of HPP in adults is wide: ranging from the severely affected—who commonly have osteomalacia—through to the minimally affected. The former typically have biallelic and the latter, heterozygous ALPL mutations. We have reviewed reports of fractures in adults with genetically proven HPP which suggest that the risk of fracture is at least 200‐fold greater in those with biallelic mutations. We also discuss two cases of postmenopausal women with heterozygous ALPL mutations. One had fractures and severe osteoporosis, but histology revealed no evidence of osteomalacia. The second had taken alendronate for 8 years, but despite profound suppression of bone turnover, histology again revealed no evidence of osteomalacia. The management of adults with HPP who have coexisting osteoporosis is challenging. More data are clearly needed, but we suggest that the risks of bisphosphonate therapy may be relatively low in patients who have heterozygous mutations and no histological evidence of osteomalacia. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.